Creating potential agricultural clusters in the Northern Great Plain Region - Micskei, Péter (Acta Agraria Debreceniensis, 2012)
The crisis of the hungarian agricultre is continuous since the ’80s. The compensation is made a dual farm system, which has created barriers to efficient agricultural production. It is confirmed by the economic indexes as well. But the most important natural resources of our country is still the land. Over the past 20 years, the government was not able to work out strategic aims and adequate system for the hungarian agriculture. In the past three decades the clusters has become the most common tool in economic development worldwide. Clusters always base on some local knowledge, and a country can be competitive on the industry in which the resources are concentrated. So the question is, is it possible to „clusterize” theagriculture and through this develop the rural economic.